ANALYSIS OF THE EFFECT OF SITUATIONAL LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE - Yayu Humairoh; Moh. Sutoro; Basrowi Basrowi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Civil Servant Performance at the Population and Civil Registration Office of Serang Regency is an important aspect in supporting the effectiveness of public services. Improving the quality of service, discipline, and employee job satisfaction requires leadership support that is able to adapt to organizational conditions and needs. This study aims to analyze the influence of situational leadership and work discipline on employee performance, both directly and through job satisfaction as a mediating variable. The method used is a quantitative approach with an associative research type. The population and sample in this study amounted to 91 Civil Servants at the Population and Civil Registration Office of Serang Regency with a saturated sampling technique. Data collection was carried out through a questionnaire using a five-point Likert scale. Data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of the SmartPLS 4.0 application. The results of the study indicate that situational leadership has a positive and significant effect on employee performance and job satisfaction. Work discipline has a positive and significant effect on job satisfaction, but does not significantly affect employee performance. Job satisfaction does not significantly affect employee performance and is unable to mediate the relationship between situational leadership and work discipline on employee performance. These findings indicate that improvements in employee performance are predominantly influenced by the implementation of effective situational leadership.